A Case of Chondrosarcoma Arising in the Temporomandibular Joint - Tsutomu Nomura; Tadaharu Kobayashi; Susumu Shingaki; Chikara Saito (Case Reports in Otolaryngology)
Chondrosarcoma is a malignant tumor originating in cartilaginous cells. And there are only few reports of the case of chondrosarcoma in temporomandibular joint. We discuss a case of chondrosarcoma in temporomandibular joint in a 28-year-old man. Tumor was in contact with the dura, but en bloc resection was performed. After surgical resection of the tumor, face defect was reconstructed by rectus abdominis-free flap. And there is no recurrence after ten years from the resection.